ANALYSIS GENDER EQUALITY IN THE PERSPECTIVE OF JAVANESE CULTURE AT KEDAULATAN RAKYAT AND HARIAN JOGJA - Sakti, Muhammad Fathurrahman Prima; Syarif, Humaira Lathifah Faridah (Journal Pena Wimaya, 2025)
Javanese culture is patriarchal culture, while Yogyakarta as the center of Javanese culture offers a unique context to study gender equality influenced by Javanese culture. This study aims to explore Javanese cultural values in local media and their impact on gender equality at Kedaulatan Rakyat and Harian Jogja, both news agencies have a close relationship with Javanese culture. This research employs in-depth interviews with the chief editors and journalists from both media outlets to understand how Javanese cultural values are implemented in news reporting practices and workplace interactions. The findings reveal that both media outlets uphold Javanese cultural values, reflected in respectful and polite reporting styles, as well as in harmonious and respectful workplace relationships. Career opportunities at both media outlets are based on individual performance and competence, regardless of gender. However, the study also found that, despite Javanese culture's tendency towards patriarchy, there is a significant shift towards gender equality. This is evidenced by the increasing number of female journalists occupying strategic and important positions within the media organizations. These findings indicate that cultural values can adapt and evolve over time to support gender equality. This research supports Indonesia's efforts to achieve Sustainable Development Goal (SDG) 5.Keywords: Gender Equality, Javanese Culture, Local Media, Kedaulatan Rakyat, Harian Jogja, SDG 5.